Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Pressure-assisted isolation of micro- and nanoplastics from food of animal origin with special emphasis on seafood - Julia Süssmann; Elke Walz; Birgit Hetzer; Ralf Greiner; Elke Kerstin Fischer; Sascha Rohn; Jan Fritsche (Journal of Consumer Protection and Food Safety, 2025)
Recent studies have indicated the presence of micro- and nanoplastics in food of animal origin. To address the concerns regarding human dietary plastic uptake, extensive monitoring using validated analytical methods is required. However, a major challenge in analysis lies in the high complexity of preparing food samples rich in macromolecular content (e.g., proteins, complex lipids), such as seafood. Consequently, this study aimed to optimise sample preparation methods for seafood, meat, milk, honey, and eggs, ensuring negligible impact on plastic integrity. Sample matrices were digested using combinations of alkaline, oxidative, and enzymatic approaches, with incubation periods ranging from 6 to 16 h. Particles were rapidly isolated by pressure-assisted filtration, which retained particles in the lower micron range. This method, used for isolating microplastic from food, was compared to the commonly employed vacuum filtration technique. Pressure-assisted filtration improved filtration rates and matrix removal while demonstrating comparable impact on procedural contamination and polymer integrity to vacuum filtration. The feasibility of microplastic analysis was demonstrated using fluorescence imaging. In contrast to microplastics, nanoplastics (< 1 µm) have greater potential for negative biological effects due to their small size, warranting detailed analysis. However, their low particle mass, susceptibility for agglomeration, and the detection limits of conventional spectroscopic techniques pose unique analytical challenges. Addressing these challenges is essential for developing standardised methodologies, including certified food reference material, to enable safety assessments of micro- and nanoplastic in food. Graphical Abstract

Towards an assessment of psychosocial work factors in a multi-level mental health intervention in the workplace: results from the MENTUPP pilot-study - Fotini Tsantila; Reiner Rugulies; Evelien Coppens; Hans De Witte; Ella Arensman; Abdulla Kahar; Arlinda Cerga-Pashoja; Paul Corcoran; Lars De Winter; Birgit Greiner; Eve Griffin; Bridget Hogg; et al. (International Archives of Occupational and Environmental Health, 2024)

The effects of different types of organisational workplace mental health interventions on mental health and wellbeing in healthcare workers: a systematic review - Birgit Aust; Caleb Leduc; Johanna Cresswell-Smith; Clíodhna O’Brien; Reiner Rugulies; Mallorie Leduc; Doireann Ni Dhalaigh; Arilda Dushaj; Naim Fanaj; Daniel Guinart; Margaret Maxwell; Hanna Reich; et al. (International Archives of Occupational and Environmental Health, 2024)
Objective To determine if and which types of organisational interventions conducted in small and medium size enterprises (SMEs) in healthcare are effective on mental health and wellbeing. Methods Following PRISMA guidelines, we searched six scientific databases, assessed the methodological quality of eligible studies using QATQS and grouped them into six organisational intervention types for narrative synthesis. Only controlled studies with at least one follow-up were eligible. Results We identified 22 studies (23 articles) mainly conducted in hospitals with 16 studies rated of strong or moderate methodological quality. More than two thirds (68%) of the studies reported improvements in at least one primary outcome (mental wellbeing, burnout, stress, symptoms of depression or anxiety), most consistently in burnout with eleven out of thirteen studies. We found a strong level of evidence for the intervention type “Job and task modifications” and a moderate level of evidence for the types “Flexible work and scheduling” and “Changes in the physical work environment”. For all other types, the level of evidence was insufficient. We found no studies conducted with an independent SME, however five studies with SMEs attached to a larger organisational structure. The effectiveness of workplace mental health interventions in these SMEs was mixed. Conclusion Organisational interventions in healthcare workers can be effective in improving mental health, especially in reducing burnout. Intervention types where the change in the work environment constitutes the intervention had the highest level of evidence. More research is needed for SMEs and for healthcare workers other than hospital-based physicians and nurses.

Correction: Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)

Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)
Objective Multicomponent interventions are recommendable to achieve the greatest mental health benefits, but are difficult to evaluate due to their complexity. Defining long-term outcomes, arising from a Theory of Change (ToC) and testing them in a pilot phase, is a useful approach to plan a comprehensive and meaningful evaluation later on. This article reports on the pilot results of an outcome evaluation of a complex mental health intervention and examines whether appropriate evaluation measures and indicators have been selected ahead of a clustered randomised control trial (cRCT). Methods The MENTUPP pilot is an evidence-based intervention for Small and Medium Enterprises (SMEs) active in three work sectors and nine countries. Based on our ToC, we selected the MENTUPP long-term outcomes, which are reported in this article, are measured with seven validated scales assessing mental wellbeing, burnout, depression, anxiety, stigma towards depression and anxiety, absenteeism and presenteeism. The pilot MENTUPP intervention assessment took place at baseline and at 6 months follow-up. Results In total, 25 SMEs were recruited in the MENTUPP pilot and 346 participants completed the validated scales at baseline and 96 at follow-up. Three long-term outcomes significantly improved at follow-up ( p < 0.05): mental wellbeing, symptoms of anxiety, and personal stigmatising attitudes towards depression and anxiety. Conclusions The results of this outcome evaluation suggest that MENTUPP has the potential to strengthen employees’ wellbeing and decrease anxiety symptoms and stigmatising attitudes. Additionally, this study demonstrates the utility of conducting pilot workplace interventions to assess whether appropriate measures and indicators have been selected. Based on the results, the intervention and the evaluation strategy have been optimised.

Characterisation of iron oxide-containing pearlescent pigments used as food colourants: nano-labelling required in the EU? - Birgit Hetzer; Volker Gräf; Elke Walz; Ralf Greiner (Food Additives & Contaminants: Part A, 2022)

Characterisation of TiO 2 -containing pearlescent pigments with regard to the European Union labelling obligation of engineered nanomaterials in food - Birgit Hetzer; Volker Gräf; Elke Walz; Ralf Greiner (Food Additives & Contaminants: Part A, 2021)

Anatomical and physiological evidence for polarisation vision in the nocturnal bee Megalopta genalis - Birgit Greiner; Thomas W. Cronin; Willi A. Ribi; William T. Wcislo; Eric J. Warrant (Journal of Comparative Physiology A, 2007)

A neural network to improve dim-light vision? Dendritic fields of first-order interneurons in the nocturnal bee Megalopta genalis - Birgit Greiner; Willi A. Ribi; Eric J. Warrant (Cell and Tissue Research, 2005)

Neural organisation in the first optic ganglion of the nocturnal bee Megalopta genalis - Birgit Greiner; Willi A. Ribi; William T. Wcislo; Eric J. Warrant (Cell and Tissue Research, 2004)

Retinal and optical adaptations for nocturnal vision in the halictid bee Megalopta genalis - Birgit Greiner; Willi A. Ribi; Eric J. Warrant (Cell and Tissue Research, 2004)